The modern treatment of nervous and mental diseases - White, William A. (William Alanson), 1870-1937; Jelliffe, Smith Ely, 1866-1945 (Lea & Febiger, 1913)
This volume, devoted to the treatment of nervous and mental diseases, is designed to meet the needs which the rapid advances in knowledge of neurology and psychiatry have created. The nervous system is here regarded as a whole and as inclusive of the mind, and it is maintained that disturbances of any and all of its functions, mental as well as physical, are proper subjects for therapeutics. The present work lays emphasis upon the psychical side of life as being worth quite as much consideration as the physical. It sets forth doctrines of nervous and mental hygiene, reconstructive factors in social organization as applied to human ills, and endeavors to present a broad front to the pessimistic nihilism in therapeutics that has been too long current in these fields, because the doctor's eyes have been too closely focused on the individual examples and results of human accidents. Neurology and psychiatry offer the widest possible opportunities for preventive medicine as well as for therapeutic optimism. The program here presented is essentially therapeutic. Planned as it has been on a broad scale, the more practical issues confronting the clinician have, nevertheless, been fully met. The editors have sacrificed philosophical views for more definite guideposts wherever, in the present state of our knowledge, such a course seemed wiser. (PsycINFO Database Record (c) 2005 APA, all rights reserved)